Efforts to Prevent Covid 19 Transmission with Health Advice in the district of Medan Belawan - Imelda, Fatwa; Nasution, Diah Lestari (Talenta Publisher, 2021)
The continued increase in the number of COVID-19 cases in the city of Medan, makes there no longer any green zone for the spread of the corona virus. Based on data from the Medan City COVID-19 Task Force, on Thursday (16/4/2020) at 21.00 WIB, now 8 of the 21 sub-districts in Medan City are in the red zone for the spread of the corona virus, while 13 other sub-districts are in the yellow zone status. Medan Belawan is still in the yellow zone status but has a big risk of being exposed to the COVID-19 virus because it is a sea transportation route. The red zone is an area with more than 10 patients under surveillance (PDP), the yellow zone is 1-10 cases, and the green zone is 0 cases. The Medan Belawan area is the largest sea transportation route in Sumatra originating from National and International which are at high risk of being exposed to covid 19. The majority of Medan Belawan residents work as fishermen and odd jobs so that the majority of Medan Belawan residents have lower middle economic levels, because of the lower middle economic level. income every day for daily life, so from the survey conducted by the field team, the majority did not carry out government recommendations such as staying at home. The purpose of this community service is Efforts to Prevent the Transmission of Covid 19 with Health Advice in Medan Belawan District. Special target: this community service is carried out for residents of Medan Belawan District. It consists of 3 activities, namely the first activity is to socialize the prevention of covid 19 transmission by distributing leaflets to community members and attaching them in public places, the second is to increase public awareness to use masks, namely by distributing 500 pcs cloth masks, the third activity is to increase public awareness of cleanliness by frequently washing hands, namely by providing portable hand washing facilities in 2 public places, namely in front of the Medan Belawan sub-district office. , and in front of Belawan Traditional Market. This community service activity is our obligation as educators in carrying out the Tri Dharma of Higher Education so that it is hoped that the Covid 19 Transmission Prevention Efforts with Health Advice in Medan Belawan District can help minimize the increase in the transmission rate of the Covid 19 virus in the community, and can reduce the death rate from cases the pandemic that is engulfing our country. The result of this service is Publishing Cinematography Rights with the title Prevention of Covid-19 Transmission with Health Advice in Medan Belawan District No. 000201509 Publication of Mass Media on September 1, 2020 in Analytical Newspaper, Metro Online Newspaper, Metro Indo Newspaper. Co.id, People's Minbar Newspapers and products in the form of: (Leaflets, Masks and Portable Hand Washing Facilities),